Empowering Households through Waste Bank Development Integrated with WhatsApp-Assisted Digital Recording and Financial Literacy Training in Sukamanah Village, Cianjur Regency, West Java, Indonesia - Riza Andrian Ibrahim; Dede Irman Pirdaus (Research Collaboration Community (Rescollacom), 2026)
Household waste remains one of the most persistent environmental problems in Indonesia, with domestic waste contributing more than half of the nation's total waste generation. Waste banks (bank sampah) have been widely promoted as a community-based solution that combines waste separation with economic incentives, yet many existing programs struggle with low and inconsistent community participation, largely due to manual, non-transparent recording systems and limited financial management skills among members. This community service program was implemented in Sukamanah Village, Cianjur Regency, West Java, with the objective of establishing a community-based waste bank integrated with a low-cost, WhatsApp-and-Google-Sheets-based digital recording system, combined with structured financial literacy training for housewives (ibu rumah tangga) as the primary participants. Unlike previous digital waste bank initiatives that rely on dedicated mobile applications requiring stable internet infrastructure and intensive technical training, this program offers a low-technology, replicable model suited to villages with limited digital literacy. The program was implemented through a participatory action research approach across four stages: preparation, socialization, training and implementation, and monitoring-evaluation, involving 42 housewives as active participants over an eight-week operational period. Results indicated a significant increase in participants' knowledge of waste segregation, the 3R concept, and basic financial management (pre-test mean 54.3; post-test mean 84.6), an active participation rate of 83%, a cumulative diverted waste volume of 612.4 kilograms, and total member savings of IDR 3,845,000. The integration of digital recording and financial literacy training strengthened transparency, trust, and continuity of member participation compared with conventional manually managed waste banks. This study contributes a practical, low-cost, and replicable model for sustainable community-based waste management that can be adapted by other rural and peri-urban villages in Indonesia facing similar infrastructural and financial-literacy constraints.